Permasalahan Budaya Membaca di Indonesia (Studi Pustaka Tentang Problematika & Solusinya) - Lilik Tahmidaten; Wawan Krismanto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Reading is one of the language skills that must be mastered by every student, the ability to read becomes one of the mandatory components in the national education curriculum. However, assessment programs of various international institutions and the Ministry of Education & Culture show that students in Indonesia are still low in their reading ability, in this case reading comprehension skills. For this reason, through this literature study, the problems and solutions are examined based on various library sources. The results of the literature study show that there are different standards between the teaching of reading in education in Indonesia and the standards used by various international institutions in measuring students' reading skills. In addition there are various factors driving the low ability & reading culture of students in Indonesia, namely: 1) Reading has not become a necessity, let alone become a culture, 2) Misperception about the concept of reading ability in most societies including students and teachers, 3) Capacity building reading is still perceived as part of the responsibility of language courses only, 3) The learning process still does not utilize models, methods, learning strategies that are diverse and suitable for reading comprehension learning, 4) reading material, learning activities and practice / evaluation questions there are teaching materials in schools that tend to still dwell on low order thinking skills, 5) Not yet the maximum facilities and infrastructure of school libraries as a center for developing the ability and culture of reading students, and 6) Program of Gerakan Literasi Sekolah (GLS) has not shown the progress expected to build a reading culture.